The MatLab Software Application for Electrical Engineering Simulations and Power System - Lessa, Leonardo da S.; Prado, Afonso J.; Silva, Rodrigo Cleber; Kurokawa, Sérgio; Bovolato, Luiz F.; Filho, José Pissolato (IntechOpen, 2012)
None